2020
DOI: 10.1038/s41419-020-02737-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted inhibition of endothelial calpain delays wound healing by reducing inflammation and angiogenesis

Abstract: Wound healing is a multistep phenomenon that relies on complex interactions between various cell types. Calpains are a well-known family of calcium-dependent cysteine proteases that regulate several processes, including cellular adhesion, proliferation, and migration, as well as inflammation and angiogenesis. CAPNS1, the common regulatory subunit of Calpain-1 and 2, is indispensable for catalytic subunit stabilization and activity. Calpain inhibition has been shown to reduce organ damage in various disease mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…The formation of new blood vessels through angiogenesis is the key to wound healing. Insufficient angiogenesis not only leads to reduced blood flow and oxygen but also restricts the entry of inflammation cells including macrophages into the wound, leading to delayed wound healing [ 26 ]. In the wound treated using SXYH ointment, the formation of new blood vessels was more obvious than in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The formation of new blood vessels through angiogenesis is the key to wound healing. Insufficient angiogenesis not only leads to reduced blood flow and oxygen but also restricts the entry of inflammation cells including macrophages into the wound, leading to delayed wound healing [ 26 ]. In the wound treated using SXYH ointment, the formation of new blood vessels was more obvious than in the control group.…”
Section: Resultsmentioning
confidence: 99%
“…The initial inflammation is a key phase in the wound healing process, which partially triggers the angiogenic response by producing high levels of VEGF [21,22]. Macrophages have a controversial role in the wound healing process: they can influence the outcome either towards a minimum scar tissue or to an impaired healing wound, as a function of the balance between the occurrence of inflammatory (M1) and reparatory (M2) macrophage phenotype [23,24].…”
Section: Discussionmentioning
confidence: 99%
“…It is generally known that autophagy can be pharmacologically induced by inhibiting mTOR with rapamycin, whereas 3-MA inhibits autophagy by targeting the class III PI3K involved in autophagosome formation [55]. IL-1β, IL-6, and ICAM-1 are important proinflammatory molecules, which play crucial roles in the preliminary inflammatory response and endothelial dysfunction [56]. Our results showed that rapamycin could partially reverse the upregulation of IL-1β, IL-6, and ICAM-1 induced by oxLDL/β2GPI/anti-β2GPI complex, while the 3-MA treatment resulted in increased expressions of inflammatory cytokines.…”
Section: Discussionmentioning
confidence: 99%